Study of Antibiotic-Resistant Bacteria and Effect of Sepsis in Heart Failure Patients in Karbala - Al-Rubaiy, Sara Saeed Hassan; Al-Daamy, Alaa Abdul Hussein; Alhidari, Ahmed Q. (Kerbala Journal of Nursing and Health Sciences., 2025)
Heart failure (HF) can be defined as a complex clinical syndrome, which might result from any structural or functional heart disorder affecting the ventricular filling or the ejection of blood into systemic circulation. Sepsis represents a potentially fatal organ infection that results from a dysregulated host organ response to infections. Finding the most prevalent bacterial species causing sepsis in HF patients and figuring out their pattern of antibiotic susceptibility in Karbala city were the goals of the presented research. Methods: The research was conducted at the Imam Hussain Medical City Hospital's Heart Center in Karbala between January and August of 2024. Following being admitted to the cardiac care unit, 25 patients with HF and bacterial infection and 25 patients with bacterial blood infections who did not have HF had 10 milliliters of venous blood drawn. Results: After the samples were cultured on different conditions to detect bacteria, antibiotic susceptibility testing was conducted. Were number of Gram negative bacteria =14 and Gram positive bacteria =11 in the group with infection without heart failure, while the number of Gram negative bacteria =16 and Gram positive bacteria =9 in the heart failure group with infection and the most common genius in infection group was Klebsiella pneumoniae which accounted for 8 (16%) isolates While, the most common genius in heart failure with infection group was Staphylococcus hominis which accounted for 5 (10%) isolates, all isolated species were found to be resistant to Ciprofloxacin (80%) in both groups and all isolated species were sensitive to Pefloxacin, Colistin, Ampicillin, Vancomycin, Linezolid and Streptomycin. Conclusion: The study concluded that the most common types of bacteria were Klebsiella pneumoniae and Staphylococcus hominis in the group of patients with and without heart failure, and the isolated bacteria were highly resistant to some antibiotics and highly sensitive to others.